Multiobjective Optimization Problems on Jet Bundles - Pitea, Ariana (Frontiers in Physics, 2022)
The aim of this work is to study constrained optimization problems by means of (Phi,rho)-convexity. We provide some sufficient conditions of optimality for a class of vectors of cuvilinear integrals by means of an adequate generalized convexity. Dual problems associated with this one are stated and developed, in terms of weak, strong, and converse duality results. The framework chosen here is one specific to the Riemannian geometry, namely that of first order jet bundles.